Calcium or Sodium Carbonate Influence on Calcium Sulfoaluminate Clinker Hydration - Pilar Padilla-Encinas; Ana Fernández-Jiménez (Molecules, 2025)
This work shows how the presence of calcium carbonate and sodium carbonate (5% and 20%) affects the hydration of a commercial calcium sulfoaluminate clinker (KCSA). For this study, water-hydrated pastes were prepared and the mechanical compressive strength and hydration rate were determined. The hydration products were characterised by XRD, DTA/TG, FTIR and SEM. The incorporation of CaCO3 can have a beneficial effect on the development of the mechanical strength of KCSA, especially at 90 days. It does not significantly alter the hydration kinetics and the hydration products formed are mainly ettringite and AH3. However, sodium carbonate has a detrimental effect, slowing down the hydration kinetics and reducing the development of mechanical strength, especially at early ages. The 20% Na2CO3 favours the formation of calcium aluminate, gaylusite and thenardite over ettringite. These phases are metastable in the presence of sodium and decompose to form calcite, alumina gel and a large amount of thenardite, which leaches out as efflorescence, causing microcracks and loss of strength in the material.